Gemini spectroscopy of ultracompact dwarfs in the fossil group NGC 1132 - Madrid, Juan P. (2013)
A spectroscopic follow-up of ultracompact dwarf (UCD) candidates in the fossil group NGC 1132 is undertaken with the Gemini Multi Object Spectrograph. These new Gemini spectra prove the presence of six UCDs in the fossil group NGC 1132 at a distance of D ∼ 100 Mpc and a recessional velocity of vr = 6935 ± 11 km s−1. The brightest and largest member of the UCD population is an M32 analog with a size of 77.1 pc and a magnitude of MV = −14.8 mag with the characteristics in between those of the brightest UCDs and compact elliptical galaxies. The ensemble of UCDs have an average radial velocity of vr = 6966 ± 208 km s−1 and a velocity dispersion of σv = 169 ± 18 km s−1 similar to the one of poor galaxy groups. This work shows that UCDs can be used as test particles to determine the dynamical properties of galaxy groups. The presence of UCDs in the fossil group environment is confirmed and thus the fact that UCDs can form across diverse evolutionary conditions.